Handbook of high-order optical modulations signal and spectra for coherent multi-terabit optical fiber transmission - Bottacchi, Stefano
This book highlights many fundamental aspects of optical fiber transmission engineering while also focusing on current state of the art applications and working examples of digital coherent optical communications. Major engineering themes are reviewed and analyzed in this book, including spectral and time-domain characteristics of multi-level pseudo-random PAM signals, optical QAM and SSB complex modulations and impulse response engineering of linear amplifiers used in next-generation Gbaud transmission systems. This book is balanced between theoretical and numerical simulation approaches, showing numerous working examples developed in Matlab. Presents an in-depth analysis of pseudo-random multi-level signals and high-order complex modulations to support coherent terabit transmission systems; Provides a unified approach to challenging engineering issues encountered in the design of Giga-baud coherent optical transmission systems using high-order complex modulation formats; Reviews engineering themes and provides in-depth analysis, modeling and quantitative examples and solutions of state of the art and future applications.